PEMBANGUNAN KINCIR AIR UNTUK PEMBANGKIT LISTRIK DAN PENGGILINGAN TEPUNG BAGI MASYARAKAT DI KAMPUNG NGALAU RANDAH KABUPATEN SOLOK SELATAN, SUMATERA BARAT - Asep Neris Bachtiar; Ahmad Fauzi Pohan (LPPM Universitas Andalas, 2024)
The need for energy, especially electricity, is fundamental and essential in daily life. This is particularly true for communities in rural areas that rely on fossil fuel-powered machines for their work, such as milling rice into flour. One such community is the farming group in Kampong Ngalau Randah, Solok Selatan, West Sumatra. This activity aims to realize the construction of a small-scale renewable energy technology building, specifically a pico-hydro power plant using a steel waterwheel that functions as both a power generator and a production machine/flour mill driver. The target partners for this activity are the residents of Kampung Ngalau Randah, Jorong Manggih, which is an isolated village in Kenagarian Pakan Rabaa Timur, Solok Selatan Regency, West Sumatra. The methods of this activity include surveys and experiments, starting with a potential survey at the partner's location followed by outreach, fabrication of the waterwheel components and assembly in the city of Padang, dismantling the old waterwheel at the partner's location, and transporting the new waterwheel unit to the partner's location, which is 180 km away. The outcome of this activity has successfully resulted in the construction and donation of a waterwheel unit for the local community. In the future, it is hoped that the development of this waterwheel-driven power plant in Kampung Ngalau Randah will serve as a pilot project that can inspire other village communities to build power plants in their respective areas.